Knowledge about chronic obstructive pulmonary disease among physicians, nurses and students at a regional hospital in Nepal - Gungner, Malin; Säll, Olof; Adhikari, Tara Ballav; Högman, Marieann (Nepalese Respiratory Journal, 2024)
Introduction: In 2019, Nepal had the highest mortality from chronic obstructive pulmonary disease (COPD) globally, and the prevalence of COPD in Nepal is expected to increase. Available research shows that the knowledge of COPD among patients in Nepal is poor and that the practice of COPD management among healthcare personnel needs to improve. Objectives: To assess the knowledge of COPD among healthcare personnel at a regional hospital and students at a local School of Health Science. Methods: A cross-sectional, questionnaire-based study was conducted among healthcare pro- fessionals and students in Tansen, Palpa district, Nepal. Scoring was based on a scale of up to 12 points, with a result of 10 points or above considered satisfactory knowledge. Results: A total of 56 healthcare workers and 208 students participated in the survey. All participants' median (IQR) score was 98,10. Among healthcare professionals, the level of knowledge was below expected on questions regarding vaccinations to prevent pneumonia and spirometry to set the diagnosis. The time spent in the healthcare profession did not increase knowledge scores. Second- and third-year nursing students had a statistically significantly higher level of knowledge than first-year nursing students. Conclusions: While healthcare personnel showed a high degree of skills in several aspects of COPD knowledge, significant gaps persist, highlighting areas for improvement in COPD care within Nepal.